Links with body image concerns, binging, and compensatory behaviours around eating. Issue 1 (2nd January 2016) - Exline, Julie J.; Homolka, Steffany J.; Harriott, Valencia A.
Abstract : Many people experience divine struggle – negative thoughts or feelings about God. This study examined connections between divine struggle (anger toward God; concern about God's disapproval), body image concerns, binge eating, and compensatory behaviours (purging, fasting, exercise) among undergraduates ( N = 413; 47% women). Measures of divine struggle showed weak, inconsistent links with binge eating but consistent positive links with body image concerns and compensatory behaviours. These associations were not moderated by gender and remained significant when controlling 16 relevant variables (e.g., personality, self-concept, depression, religiousness). Body image/eating variables explained 9–11% of variance in current divine struggles. Binging correlated positively with protest and anger suppression toward God but also with approach behaviours. Compensatory behaviours correlated positively with protest, disengagement, and anger suppression. Spiritual grandiosity – seeing oneself as having a special/superior relationship with God – predicted more compensatory behaviours. Some nonbelievers also reported divine struggles, and these were associated with body image/eating disturbances.